JAWABAN PAT
QUESTIONS 1
QUESTIONS 2
QUESTIONS 3
15). 5^x+2 < 4^x
log5^x+2 < log4^x
(x+2) log5 < x (log4)
xlog5 + 2log5 < xlog4
xlog5 - xlog4 < -2 log5
x (log5 - log4) < -2log5
HP = {x < -2log5 /log5-log4}
16). (x-4)^4x < (x-4)^1+3x
4x < 1+3x
x < 1
HP : {x < 1 atau x < 4}
x-4 < 0
x < 4
17). 2^x³-x < 1
2^x³ - x < 2^0
x³ - x < 0
x (x - 1) (x + 1) < 0
x = 0, x = 1, x = -1
HP : {0 < x < 1 atau x < -1}
18). 5^2x+1 > 5^x+4
(5^x)² × 5¹ > 5^x + 4
5 p² > p + 4
5p² - p - 4 > 0
(p - 1) (5p + 4) > 0
p = 1 p = -4/5
HP : {x < -4/5 atau x > 1}
19). 2^x × 2¹ × 2^-4 ≤ 0 / 1-2^x
p - 2p - 4 / 1-2x ≤ 0
(p-2) (p+1) / p (1-p) ≤ 0
p = 2 p = -1
HP : { -1 < x < 2}
20). (4^x)² × 4¹ > 4^x + 3
4p² - p - 3 > 0
(4p - 4/4) (4p +3) > 0
(p - 1) (4p + 3) > 0
p = 1 p = -3/4
HP : {-3/4 < x < 1}
21). 3^x-2y = 3^-4
x - 2y = -4
x - y = 4
__________________ -
-y = 8
y = -8
x-8 = 4
x = 12
x+y = 12 + (-8) = 4
22). (2a^5 - b^-5)/3 × 2a^9 × b^-1) ^-1
(2¹a^5 b^-5/2^5 a^9 b^-1)
(2^-4 a^-4 b^-4)
(2^⁴ a^⁴ b^⁴)
(2 ab)⁴
23). 9^3x-4 = 81^½x-5
(3²)^3x-4 = (3^-4)^2x-5
6x - 8 = -8x + 20
14x = 28
x = 2
24). 4¹+² × 3^4x+1 < 432
4 × 4^2x × 3^4x × 3 < 432
4^2x × 3^4x < 36
16^x × 18^x < 36
1.296^x < 36
36^x < 36
x < 1
25). (1/3)^x+2 < (1/3)^x
x + 2 < x
0 < 2 (TIDAK MEMENUHI)
(1/3)^x+2 < (1/3)^-x
x +2 < -x
2x < -2
x < -1
QUESTIONS 4
32. g = ( 2, 1, -3 ) h = ( -1, 3, -2 )
ǀ g ǀ = √14 ǀ h ǀ = √14
Cos Ɵ = g.h / ǀ g ǀ. ǀ h ǀ
= -2 + 3+6 / √14. √14
= 7/14
= 1/2
33.
45 + 4√5 = ǀu + v ǀ
ǀu + v ǀ = 53,944 = 54
34. 34. AB = B – A
AB + A = B
(-15, 12 ) + (-4, -6 ) = B
(-19, 6 ) = B
35. C = u.v / ǀvǀ . v
= -6 + 2 + (-3) / (√14)2 . ( -3i + 2j – k )
= -7/14 . ( -3i + 2j – k )
= -1/2 . ( -3i + 2j – k )
= ( 3/2i -j + 1/236 4
= 14 + 90 -11m / √4+100+121
4 = 104 – 11m / √225
4 = 104 – 11m / 15
60 = 104 – 11m
11m = 104 – 60
11m = 44
m = 4k
37. p . q = | p | | q | cos Θ
p . q = (-3i - 3aj - bk ) . ( -ai + bj - 2ak )
p . q = 3a - 3ab + 2ab
p . q = 3a
| p |² = (-3)² + (-3a)² + (-b)² = 9 + 9a² + b²
| p | = √ (9 + 9a² + b² )
| q |² = (-a)² + b² + (-2a)² = a² + b² + 4a²
| q | = √ (a² + b² + 4a² ) = √(5a²+b²)
r = [ ( p . q ) / (| q |²) . q
i - j + 2k = [ 3a /(5a²+b²) . ( -ai + bj - 2ak )
-3 = 3a² /( 5a² + b² )
-3a² - b² = 3a²
-b² = a²
cos Θ = p . q / ( | p | | q | )
(√6)/8 = 3a / ( √ (9 + 9a² + b² ) . √(5a²+b²)
[ (√6)/8 ]² = (-3b)² / (9 - 9b² + b² ) . (-5b²+b²)
( 6 / 64 ) (9 - 8b²) . (-4b²) = 9b²
( -24 / 64 ) (9 - 8b²) = 9
-8b²+ 9 = -24
-8b² = -33
b² = 4,125
b = √4,125
b = 2,03
maka, b = -a = -2,03. Jadi, nilai a = -2,03
Komentar
Posting Komentar